Improving Students' Science Process Skills through the Application of Learning Models Discovery Learning in Senior High School - Waruwu, Ofeni; Azhar, Azhar; Rahmad, M. (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This study aims to describe the improvement of learning outcomes of students' science process skills by applying the Discovery Learning model. This research method uses Classroom Action Research which is carried out over a period of three months, where each cycle contains stages of planning, implementing, observing, and reflecting on the actions given. The research subjects were class XI MIPA 1 students with a total of 32 people. The data collection method uses a student science process skills learning outcomes test, which includes ten indicators: observation, grouping, interpreting, predicting, asking, hypothesizing, utilizing tools/materials, conducting experiments, applying concepts, and communicating. The results showed that the average student learning outcomes in the first cycle were obtained at 65.94 with a classical completeness of 68.75% (sufficient category) and an N-Gain Score of 0.37, and cycle II obtained an average student learning outcome of 86.09 with a classical completion of 100% (excellent category) and an N-Gain Score of 0.60. Student learning outcomes between cycle I and cycle II show that through the application of the learning model, discovery learning effectively improves students' science process skills.